IMPLEMENTASI DETERMINISTIC FINITE AUTOMATA (DFA) PADA PERANCANGAN APLIKASI PERHITUNGAN UANG HARIAN PERJALANAN DINAS KEMENTERIAN - Deny Robyanto; Ade Priyatna Priyatna; Eni Heni Hermaliani; Frieyadie Frieyadie; Windu Gata (Teknik Informatika, 2021)
Each ministry always has a budget for official travel, especially for the daily money given to personnel who travel in exchange for daily expenses. With the current pendemi need to be held an application system that can reduce contact when handling official travel files. The design of this application will use the implementation of Deterministic Finite Automata (DFA) as an abstract machine to determine the state or stages to determine the transition between these stages to determine the daily money calculation of official travel. From the calculation of daily money will be made recapitulation to be verified and if it is considered appropriate and correct will be transferred to the account that travels to the office. This is the role in making abstract machines for the calculation of daily money using Deterministic Finite Automata (DFA) because each stage is right to one stage next until the last stage that prints proof of transfer.